Ứng dụng mô hình giá trị, thái độ và hành vi trong nghiên cứu hành vi mua hàng xanh của người tiêu dùng ở Việt Nam - Nguyễn Viết , Bằng; Bùi Hồng , Linh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
Consumers are becoming increasingly aware of the environmental and social consequences of their purchases. This study investigates the factors driving green purchase behavior based on the value–attitude–behavior (VAB) model. The paper follows a quantitative approach through a survey of 333 consumers. According to the findings, attitudes toward environmental issues, attitudes toward eco-social benefits, and green product information have significant positive influences on green purchasing behavior. Furthermore, the results reveal the relationship between environmental consciousness, green advertising, attitudes towards environmental issues and attitudes towards eco-social benefits. The findings of this study provide valuable insights into the effects of various factors on green purchase behavior.